Sistem Pakar Menentukan Kerusakan Gigi Menggunakan Metode Certainty Factor - Subhan Hartanto; Nadya Andhika Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Damage to the teeth can affect the health of other members of the body, so that it will interfere with activity. Symptoms of this disease are often not considered or considered unimportant. This also occurs in dental diseases including those that damage tooth structure and cause cavities. To find out the symptoms of tooth decay that are owned by patients, users or users only answer a few questions that exist on the Expert System web as a tool in providing consulting services like an expert through the web. The purpose of this study is to create an Expert System program that contains the knowledge of an expert who has the ability to diagnose human tooth decay based on the physical form that occurs and the taste experienced and the position of human teeth based on expert / expert knowledge (dentists) using the Certainty Factor method . This system will provide solutions and make it easier for doctors to socialize their patients.